Implementation of lean manufacturing to blend with good manufacturing practice at Minda Tulus Industries Sdn. Bhd. for improved performance - Nasry, Nasrul Ashraf; Mahmud, Khairus Syakirah; Hilmy, Irfan; M. I., Ismail; Hassan Basri, Rodziah (Knowledge Transfer Programme © Knowledge Transfer Centre, 2017)
The implementation of Lean Manufacturing System (LMS) together with the consideration of the Good Manufacturing Practice (GMP) can enhance the performance in the production as well as maintaining the highest quality of the product. The knowledge transfer program between International Islamic University Malaysia and Minda Tulus Industries Sdn Bhd involved the knowledge and awareness about the importance of LMS in enhancing the performance of the company. The knowledge transfer process was conducted through modules: lectures/briefing, practical training and also games to ensure the company, especially the workers, can fully understand the tools & techniques of LMS together with GMP can boost the performance especially in the production area. LMS training module focus on the tools and techniques of lean such as 5S, Kanban, Problem Solving Method, Value Stream Mapping (VSM), Single Minute Exchange Dies (SMED), Total Productive Maintenance (TPM) and many more. This proceeding paper unfolds the journey of this knowledge transfer programme that had been carried out over a period of 24 months from September 2014 until August 2016 and also the implication of this program towards the company, university and also the community.